External Auditing in an Enterprise Resource Planning System Enabled Environment in South Africa - Tembo, Pym Don (My University, 2014)
Enterprise Resource Planning (ERP) Systems are excellent software packages that enable businesses to integrate a variety of business functions. In particular, ERP systems have become systems of choice for many public and private companies and have radically changed the way accounting and business information is processed and audited. The challenge for auditors is to keep up with the changing nature of ERP systems and how to cope with changes that come when companies implement new ERP systems. Auditors may need to keep abreast of the changes that ERP systems bring and also modify their auditing processes and procedures to ensure that there is less risk in providing incorrect audit opinions as a result of a lack of understanding of the ERP environment. This research was conducted to investigate the impact of implementing an Enterprise Resource Planning System (ERP) System on the conventional statutory external audit process in South African companies. The research was conducted via an online questionnaire that was distributed to auditors across South Africa. In order to obtain explanations of the result findings, interviews were conducted with selected audit seniors in selected audit firms. A total of 137 questionnaire responses was collected and seven interviews done to triangulate the findings of the questionnaire. The results of this survey indicate that ERP implementation inherently changes business processes and there are audit risks that are associated with auditing ERP-enabled environments compared to non-ERP environments . The results also suggest that auditors recognise the risks associated with inter-dependencies among business processes and control vulnerabilities after an ERP implementation. ii Auditors also recognise that an overall understanding of ERP systems and different methods of auditing is a critical component of ensuring that correct opinions of the audit are formulated.
MBA thesis
Keywords: Enterprise resource planning